The stock market performance of exploration-oriented and exploitation-oriented cross-border mergers and acquisitions: Evidence from emerging market enterprises. Issue 4 (August 2020) - Zhang, Zhu; Lyles, Marjorie A.; Wu, Changqi
Highlights: Exploration-oriented acquisitions have worse stock market performance than exploitation-oriented acquisitions. Acquiring firms can reduce the risk of exploration-oriented acquisitions by having more high-discretion slack resources. Acquiring firms can reduce the risk of exploration-oriented acquisitions by maintaining a high level of equity share in the target firm. Acquiring firms perform better if they conduct exploration-oriented acquisitions in related industries. Abstract: This study builds on insights from mergers and acquisitions (M&A) studies and the perspective that stock market performance is affected by the M&A strategies of firms. Past studies show that acquisitions are an effective way to exploit existing knowledge and explore new possibilities. We argue that stock market performance can be a response to exploration/exploitation strategies in the context of cross-border M&As by emerging market multinationals. Based on cross-border M&A data of Chinese multinationals, we find that exploration-oriented acquisitions have worse stock market performance than exploitation-oriented acquisitions. Furthermore, we find support for our premise that acquiring firms can reduce the risk of exploration-oriented acquisitions by having more high-discretion slack resources or by maintaining a high level of equity share of the target firm. In addition, acquiring firms perform better if they conduct exploration-oriented acquisitions in related industries. Our results contribute to a better understanding of exploration and exploitation in the context of M&As.